2015
DOI: 10.3390/healthcare3041243
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Cognition in Community-Dwelling Older Adults: A Review of Literature

Abstract: Changes in sleep and cognition occur with advancing age. While both may occur independently of each other, it is possible that alterations in sleep parameters may increase the risk of age-related cognitive changes. This review aimed to understand the relationship between sleep parameters (sleep latency, wake after sleep onset, sleep efficiency, sleep duration, general sleep complaints) and cognition in community-dwelling adults aged 60 years and older without sleep disorders. Systematic, computer-aided searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 60 publications
(146 reference statements)
2
33
0
Order By: Relevance
“…While a meta‐analysis of case‐control studies reported that insomnia is associated with significant impairments of small to moderate magnitude in episodic memory, problem solving, manipulation and retention in working memory, no significant group differences were observed for general cognitive function, perceptual and psychomotor processes, procedural learning, verbal functions, different dimensions of attention and some aspects of executive functioning [Fortier‐Brochu et al, ]. Furthermore, the results of studies assessing the relationship between sleep quality and cognition in community‐based samples of older adults have been highly variable, with two recent reviews highlighting the inconsistency of the literature to date [Brewster et al, ; Yaffe et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…While a meta‐analysis of case‐control studies reported that insomnia is associated with significant impairments of small to moderate magnitude in episodic memory, problem solving, manipulation and retention in working memory, no significant group differences were observed for general cognitive function, perceptual and psychomotor processes, procedural learning, verbal functions, different dimensions of attention and some aspects of executive functioning [Fortier‐Brochu et al, ]. Furthermore, the results of studies assessing the relationship between sleep quality and cognition in community‐based samples of older adults have been highly variable, with two recent reviews highlighting the inconsistency of the literature to date [Brewster et al, ; Yaffe et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews on insomnia in older adults likewise conclude that the relationship of cognition and cognitive decline with complaints is inconsistent, in contrast to their relatively consistent relationship with sleep duration, sleep fragmentation, and sleepdisordered breathing (446). Moreover, in the studies that did find worse cognitive performance in insomnia, results might have been secondary to short sleep depressive symptoms, undiagnosed sleep apnea and other medical conditions (57).…”
Section: Objectively Assessed Daytime Cognitive and Emotional Functiomentioning
confidence: 99%
“…Aging changes the typical rhythm of sleep. Approximately 50 percent of the elderly suffer from sleep problems such as reduction in duration of total sleep time, decreased efficiency of sleeping, and initial and late insomnia (Brewster et al, 2015; Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%